Double-Sided Linear Iron-Core Fine-Tooth Motor for Low Acoustic Noise and High Acceleration - Yoon, Jun Young; Lang, Jeffrey H.; Trumper, David L. (IEEE/ASME transactions on mechatronics, 2019)
This paper presents the design, construction, and testing of a low-noise high-force double-sided linear iron-core motor for high-precision and high-throughput system applications such as in semiconductor photo-lithography machines. Linear iron-core permanent-magnet motors can emit significant vibration and acoustic noise due to high spatial-frequency force harmonics, causing harmonic vibrations of a moving stage. As a design solution to such motor noise, we presented magnetic designs of a new linear iron-core motor having fine teeth, narrow slots with high aspect ratio, and a moving skewed Halbach magnet array in an earlier article. In this paper, we present a further noise reduction method of directly canceling out the normal-direction force harmonics by using a symmetric double-sided motor. In the conventional iron-core motor design, the double-sided configuration achieves more than 70% overall noise reduction relative to a single-sided configuration. The new fine-tooth motor even in the single-sided configuration reduces the acoustic noise further by 79% from the double-sided conventional motor, which corresponds to 95% noise reduction compared to the single-sided conventional motor. By configuring the fine-tooth motors in a double-sided manner, we achieve more than 35 dB noise reduction in sound pressure level during acceleration regions, which corresponds to a 50:1 reduction in units of Pascals. In this paper, we also present the high-shear-stress performance of the double-sided fine-tooth motor, achieving 8.2 G with a 12.3 kg stage using only two magnet pole pairs each for the upper and lower motors.